Awareness of occupational hazards and use of safety measures among welders: a cross-sectional study from eastern Nepal - Budhathoki, Shyam Sundar (BMJ Publishing Group, 2014)
OBJECTIVE: The proper use of safety measures by welders is an important way of preventing and/or reducing a variety of health hazards that they are exposed to during welding. There is a lack of knowledge about hazards and personal protective equipments (PPEs) and the use of PPE among the welders in Nepal is limited. We designed a study to assess welders’ awareness of hazards and PPE, and the use of PPE among the welders of eastern Nepal and to find a possible correlation between awareness and use of PPE among them. MATERIALS AND METHODS: A cross-sectional study of 300 welders selected by simple random sampling from three districts of eastern Nepal was conducted using a semistructured questionnaire. Data regarding age, education level, duration of employment, awareness of hazards, safety measures and the actual use of safety measures were recorded. RESULTS: Overall, 272 (90.7%) welders were aware of at least one hazard of welding and a similar proportion of welders were aware of at least one PPE. However, only 47.7% used one or more types of PPE. Education and duration of employment were significantly associated with the awareness of hazards and of PPE and its use. The welders who reported using PPE during welding were two times more likely to have been aware of hazards (OR=2.52, 95% CI 1.09 to 5.81) and five times more likely to have been aware of PPE compared with the welders who did not report the use of PPE (OR=5.13, 95% CI 2.34 to 11.26). CONCLUSIONS: The welders using PPE were those who were aware of hazards and PPE. There is a gap between being aware of hazards and PPE (90%) and use of PPE (47%) at work. Further research is needed to identify the underlying factors leading to low utilisation of PPE despite the welders of eastern Nepal being knowledgeable of it.